Assessment of Trismus among Patients with Head and Neck Cancer - Ameer Talib Abd-Zaid; Diaa K. Al.Bayati; Ali A. Al-Fahham (Kufa Journal for Nursing Sciences)
Background: Trismus means the inability to open the mouth more than 35 mm, it is also called restriction of the mouth opening, and negatively affects eating, drinking, and speech, as well as the difficulty of the mouth cleaning. In addition, the Trismus in patients with head and neck cancer may be caused by an increase in the size of the tumor that affects the chewing muscles or tissue fibrosis as a result of surgery or radiation.